Synthesis and Configurational Studies of Some 2-Methyl-1-telluracyclohexane Derivatives - I. Ayoob, Ala'a; A.K. Al-Allaf, Talal; A. Mohammed, Salim (Asian Journal of Chemistry, 2010)
New heterocyclic tellurium compounds of the general formula (2–CH3)–C5H9-1-Te(RX), R ═ X ═ Cl, Br, I or R ═ methyl, ethyl, allyl; X ═ Cl, I or R ═ ethyl, allyl, benzyl; X ═ Br or R ═ methyl, phenyl; X ═ BPh4, have been prepared and characterized on the basis of their IR and 1H NMR spectral data. It was shown by NMR that both cis- and trans-geometrical isomers for some of these compounds are present in solution. Also all the compounds prepared showed considerable stability towards reductiveelimination reactions and do not interact with the solvent used. The molar conductivities of these compounds in DMSO and DMF indicate that there is some ion pairing.